Delayed Recovery After Deep Brain Stimulation Surgery for Parkinson's Disease Under General Anesthesia-Cases Report - Feng, Long; Liu, Yaohong; Tang, Hao; Ling, Zhipei; Xu, Longhe; Yuan, Weixiu; Feng, Zeguo (Frontiers in Surgery, 2022)
Objective: Parkinson’s disease(PD) is a neurodegenerative syndrome and deep-brain stimulation (DBS) is an effective therapy for carefully screened patients with PD. However, delayed recovery after anesthesia, which occurs after taking prolonged general anesthesia for such patients, has been reported less frequently in the literature. Case presentation Three patients with PD elective underwent DBS surgery. The first patients demonstrated walking disability, gait deficits, unstable posture, limb stiffness, and imbalance. The second demonstrated left limb static tremor, stiffness, and bradykinesia. The third demonstrated bradykinesia, rigidity, walking deficits, and decreased facial expression. These included two males and one female with a mean patient age of 60.7±6.7year, weight 63.7±11kg, height 163.3±7.6cm, and preoperative American Society of Anesthesiology rating of 2.3±0.6. The preoperative Glasgow Coma Scale mean score was 15. All patients completed the operation under general anesthesia( the meantime is 5.3±1.1h). The mean operation time was 252±60min. The mean bleeding volume was 50ml, and the urine volume was 867±569ml. However, all the patients showed unconsciousness after 95±22 minutes after stopping the anesthetic, and the respiratory function was in good condition, but they could not cooperate with anesthesiologists and had no response to the anesthesiologist's instructions. The mean hospital stay was 17±7 days. All patients were discharged uneventfully. The average number of days patients were followed up postoperatively was in 171±28.5 days. Motor and speech improved significantly postoperatively in three patients compared with preoperatively. Taking antiparkinson medication was markedly reduced. There were no complications during postoperative follow-up. Conclusions To prevent delayed recovery occurring after DBS surgery in Parkinson's disease, it is recommended to take scalp nerve block + general anesthesia to complete the procedure while avoiding general anesthesia.